Resilience redefined: a Quranic perspective through the story of Yusuf A.S. - Mohiuddin, Mohammad; Radhilufti, Nadya Farisha (IIUM Press, 2025)
It is commonly known that the concept of resilience, even though familiar to the human brain, could be challenging to implement in daily life. This paper studies the conceptualisation of resilience from two disciplinary perspectives with an emphasis on the significance of the concept through the lens of Islam. This paper is based on chapter twelve of the Quran—Surah Yusuf, which manifested and set the roots for resiliency in Islamic history. In completing this study, the methods of discourse and textual analysis were incorporated to identify, evaluate, and extract lessons of resiliency from Yusuf (Alayhissalam)’s story. A systematic analysis of various journal articles, Quranic texts and tafsirs was employed by using keywords in examining data related to the topic. Findings indicate that Western ideology acknowledges the concept of resilience as the ability to bounce back after facing adversities. On the other hand, Islamic theology argues beyond that as adversities are regarded as a “system of tests” for mankind in attaining spiritual elevation where Islam provides guidance to overcoming them. Three main sub-concepts were found from the story of Yusuf (A.S.), which became the core findings of this research in explaining the concept of resilience: (i) sabr, (ii) shukr, and (iii) taqwa. The paper presents how the three sub-concepts were implied in the life of Yusuf (A.S.) and have been proven to aid the resiliency of an individual. Therefore, this research aims to accentuate and encourage the implementation of being resilient in the life of today’s society